Upgrading Vocabulary by Crossword Puzzles Games to Improve Descriptive Text Writing Ability - Sutri Winurati; Lailatul Musyarofah; Eka Fadilah (International Journal of English and Applied Linguistics (IJEAL), 2023)
The aim of this research is to increase students' vocabulary. The previous students' vocabulary was low when measured during random drilling. Only a few students know the meaning of vocabulary words. In class 7C there are 35 students, but only 8 students can answer orally, which is around 23%. The remaining 27 students still do not understand vocabulary, namely 77% of students don’t understand. So that the use of Crossword Puzzles Game is expected to be able to upgrade the vocabularies that students have. When students have many vocabularies, students will be able to create descriptive sentence at least in accordance with the vocabulary were found in the Crossword puzzles game. In the value of Crossword Puzzles Game students get extraordinary scores. Only 1 student or 3% below the KKM 75 and 34 students or 97% of students above the KKM 75. Meanwhile, the score of the descriptive text writing made by the students scored below the KKM 75 was 4 students or 11 % and above KKM 75 there are 31 students or 86%. Thus Upgrading Vocabularies By Crossword Puzzles Game To Improve Descriptive Text Writing Ability in Class 7C SMP Negeri 2 Sukodono is proven to be true.